Focused Family Planning Counseling Increases Immediate Postpartum Intrauterine Contraceptive Device Uptake: A Quasi-Experimental Study - Wayessa MB; Abebe TW; Habtewold EM; Adlo AM; Teklu AM; Abeya SG; Negero WO (Dove Medical Press, 2020)
Muleta Befkene Wayessa,1– 3 Tilaye Workineh Abebe,1– 3 Ephrem Mannekulih Habtewold,1– 3 Abebe Megerso Adlo,2 Alula M Teklu,2,3 Sileshi Garoma Abeya,2 Wakgari Olijira Negero1– 3 1Department of Gynecology and Obstetrics, Adama Hospital Medical College, Adama, Ethiopia; 2Department of Public Health, Adama Hospital Medical College, Adama, Ethiopia; 3Center for International Reproductive Health and Training Center at Michigan University, Addis Ababa, EthiopiaCorrespondence: Muleta Befkene Wayessa Tel +251 91 788-6932Email muletawayessa@gmail.comPurpose: The aim of the study was to assess the effectiveness of focused family planning counseling (FFPC) in increasing postpartum intrauterine contraceptive device (PPIUCD) uptake among mothers who gave birth in the public health facilities of the towns of Adama and Olenchiti from April 1 to May 30, 2017.Methods: A quasi-experimental study design was employed, taking a sample of 726 postpartum mothers: 484 in the non-intervention group (NIG) and 242 in the intervention group (IG). Focused family planning counseling was given to the IG using a newly designed cue card adapted from World Health Organization (WHO) guidelines and developed based on the constructs of the health belief model. Counseling based on a routine counseling approach was given to the NIG. The interviewer administered a semi-structured questionnaire for data collection. Data were analyzed using SPSS software, version 20. Descriptive statistics were used to characterize the study participants. The difference in the proportion of PPIUCD uptake in the two groups was tested using an independent Z-test at an alpha level of 0.05. Binary logistics regression was used to identify factors associated with the odds of taking IUCD. The significance of association was declared for P-values less than 0.05.Results: The proportion of PPIUCD uptake in the IG [12.4%; 95% CI: 8.6, 17.4] was significantly higher than in the NIG [4.8%; 95% CI: 2.9, 6.7] with a P-value = 0.000. The odds of IUCD uptake among the IG was about 6 times higher (AOR: 5.92; 95% CI: 2.79, 12.60) than in the NIG. In addition, being unmarried women (AOR: 12.96; 95% CI: 4.30, 34.56), having higher education (AOR: 3.07; 95% CI: 1.13, 8.36), grand multiparity (AOR: 3.76; 95% CI: 1.58, 8.95), making a mutual decision (AOR: 0.16, 95% CI: 0.07, 0.38) and having a better knowledge of family planning (AOR: 5.92, 95% CI: 2.79, 12.60) were factors associated with uptake.Conclusion: Providing FFPC immediately increases PPIUCD uptake. The uptake was also associated with marital status, education, parity, decision and knowledge on family planning.Keywords: Adama, Ethiopia, IUCD, Olenchiti, Oromia, quasi-experimental